Erratum: Media Pembelajaran Ular Tangga dalam Keterampilan Dasar Dribbling Bola Basket - Ruslan Rusmana; James Tangkudung; Firmansyah Dlis (STKIP Muhammadiyah Kuningan, 2020)
Correction to: JUARA: Jurnal Olahraga This corrects the article DOI: https://doi.org/10.33222/juara.v4i2.527 This article was originally published using English metadata in the article title and this is our fault. but now the article metadata has been changed in Indonesian and appears correctly in the current article.